Laser welding of dissimilar alloys between high tensile steel and Inconel alloy for high temperature applications. Issue 2 (3rd April 2022) - Cheepu, Muralimohan; Kumar Reddy, Y. Ashok; Indumathi, S.; Venkateswarlu, D.
ABSTRACT: Inconel alloys are used for high temperature applications due to their excellent properties at elevated temperatures. The joining of Inconel alloys with other alloys is challenging due to the formation of cracks and interface microstructural segregation of alloying elements. In the present investigation Inconel 718 alloy was joined with high tensile steel using laser welding. In order to attain the quality joints, welding parameters were studied and identified their range. The microstructural characteristics of the welds at the fusion zone and heat-affected zone were analyzed. The microhardness variations across the fusion zone and other zones were observed. The mechanical properties of the joints were evaluated and found that the strength of the joints was related to laser power. The elemental analysis across the fusion zone was revealed the formation of segregation of the elements which has an influence on the strength of the joints.